POLITICA DE SECURITATE A REPUBLICII MOLDOVA ÎN SPAŢIUL SUD-EST EUROPEAN: AVANTAJE ŞI PERSPECTIVE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2007)
One of the most important problems within political science aims to national and international security, whose intensity and nature have hugely varied through the course of time, being sometimes characterized by an excessive spirit of confrontation and close cooperation. The collapse of the bi-polar system and suppression of the Cold War at the end of 80s has evoked certain grounds to consider that security is becoming a top concept of discussions within international post-war system. To resolve its own problems, Republic of Moldova has become an active participant of wide cooperation in the sphere with South Eastern European Countries, as they posses numerous possibilities to admonish security problems of Republic of Moldova.